A multi-institutional study of post-traumatic stress disorder and its risk factors in Ethiopian pediatric patients with physical trauma - Tadesse Tarik Tamir; Selam Fisiha Kassa; Daniel Ayelegne Gebeyehu (BMC Psychiatry, 2022)
Abstract Introduction Post Traumatic Stress Disorder (PTSD) was more common in children who had suffered physical trauma than in adults. Despite its prevalence, the prevalence and factors associated with PTSD in pediatric patients with physical trauma are unknown in Ethiopia. As a result, the purpose of this study was to determine the prevalence of PTSD and associated factors among pediatric patients with physical trauma who attended Northwest Amhara referral hospitals. Methods An institutional-based cross-sectional study design was used in 422 pediatric patients with physical trauma aged 8–18 years from March 15 to May 15/2021. Using a systematic random sampling technique, data were collected from a sample of selected trauma patients via interviews and chart review. A standardized, pre-tested Child PTSD Symptom Scale was used to assess the severity of PTSD. Epidata 4.6 was used to enter the data, and Stata 14.0 was used to analyze it. Bivariable and multivariable binary logistic regression models were used to identify PTSD determinants. Result The study included 422 paediatric patients who had suffered physical trauma, with a response rate of 97.87 percent. PTSD was found in 22.03 percent of paediatric patients with physical trauma in Northwest Amhara referral hospitals. The study discovered that female gender (AOR = 3.04, 95 percent CI: 1.58–5.84), age of 8 to 10 years old (AOR = 3.70, 95 percent CI: 1.39–9.87), having a chronic medical illness (AOR = 5.99, 95 percent CI: 2.60–13.77), having severe pain (AOR = 3.17, 95 percent CI: 1.12–8.99), low social support (AOR = 8.97, 95 percent CI: 4.04–19 were associated with PTSD. Conclusion and recommendation The prevalence of PTSD was found to be high among pediatric patients who had experienced physical trauma. Special attention should be given to female patients, aged 8 to 10 years old, who have a chronic illness, for those who complain of severe pain and engaging others to provide good social support systems, are strongly recommended to alleviate PTSD in this segment of population.